Application Of the Markowitz Model in Determining the Optimal Portfolio of Stocks Listed on The Jakarta Islamic Index (Jii) For The 2022–2024 Period - Hamzah, Muhammad Ammar; Rosyadi, Imron (PT Keberlanjutan Strategis Indonesia, 2026)
The continued increase in Indonesia's investor base, accompanied by the broader inclusion of Sharia-compliant equities as reflected in the continued advancement of the Islamic stock market. Nevertheless, participation in capital market investment remains inseparable from risk exposure. Therefore, investors need to carefully consider every investment decision when participating in the stock market. This study is intended to determine the most appropriate stock portfolio composition among companies included in the Jakarta Islamic Index over the 2022–2024 period by employing the Markowitz Model through three portfolio strategies, namely minimum risk, maximum expected return, and maximum Sharpe ratio. The research employs a descriptive quantitative design using secondary data obtained from daily stock closing prices, which are analyzed using mean–variance estimation, covariance and correlation measures, as well as portfolio performance evaluation techniques. Data analysis is conducted using Visual Studio Code with the Python programming language. The results show that the minimum risk portfolio produces the lowest level of risk through diversification across several stocks, while the maximum expected return portfolio offers the greatest return potential, although it is accompanied by a higher degree of risk because the investment is not diversified. By contrast, the portfolio with the largest Sharpe Ratio demonstrates the highest level of efficiency in balancing expected return against risk. Accordingly, a portfolio constructed using the maximum Sharpe ratio approach can be regarded as the most optimal strategy, as it provides the most advantageous balance between risk exposure and return potential.